Peningkatan Kinerja Pemasaran UMKM Melalui Dimensi Kewirausahaan di Kabupaten Kerinci - Edia Satria; Ida Yusnita; Ayu Esteka Sari (J-MAS (Jurnal Manajemen dan Sains), 2020)
Entrepreneurship is believed to be a tool to encourage economic growth to solve other economic problems, such as unemployment, poverty and social inequality. Micro, Small and Medium Enterprises is a business that plays an important role in the national economy. The success of the marketing of Micro, Small and Medium Enterprises is influenced by the dimension of entrepreneurship. The dimensions of entrepreneurship used in this study are economic entrepreneurship, resource-based entrepreneurship and human capital entrepreneurship. Respondents in this study were actors of Micro, Small and Medium Enterprises (MSMEs) in Gunung Raya Subdistrict, Kerinci Regency as many 100 respondents. The Model Testing Technique in this study used the Structural Equation Model (SEM) using AMOS. The results showed that the Entrepreneurship Dimension had a positive and significant effect on the Market Performance of MSMEs. The magnitude of the influence of entrepreneurship Dimension on Market Performance of MSMEs is 0.231 or 23.1%, so it is necessary to support entrepreneurship Dimension to increase the Market Performance of MSMEs.